Active Treatments Prolong the Survival in Patients With Hepatocellular Carcinoma and Performance Status 3 or 4: A Propensity Score Analysis. Issue 10 (November 2015) - Hsu, Chia-Yang; Liu, Po-Hong; Lee, Yun-Hsuan; Hsia, Cheng-Yuan; Huang, Yi-Hsiang; Tsai, Ya-Ju; Nagaria, Teddy S.; Lin, Han-Chieh; Huo, Teh-Ia
Abstract : Goals and Backgrounds: Best supportive care is suggested as the standard treatment for hepatocellular carcinoma (HCC) patients with performance status (PS) 3-4 by the Barcelona Clinic Liver Cancer (BCLC) system. To investigate the rationale of treatment allocation. Study: A total of 2660 HCC patients were reviewed. One-to-one matched pairs between PS 3 and 4 patients receiving supportive care and anti-HCC treatments were generated by using the propensity score with matching model. The survival analysis was performed with the Kaplan-Meier method and log-rank test. The hazard ratio was calculated with the Cox proportional hazards model. Results: Among 328 patients with PS 3-4, 38% of patients received active anti-HCC treatments against the BCLC system. Compared with patients undergoing supportive care, patients receiving anti-HCC treatments more often had milder cirrhosis, smaller tumor burden, and lower serum α-fetoprotein levels (all P <0.05). Patients undergoing supportive care had significantly decreased survival ( P <0.0001). With propensity scores, 101 pairs of similar HCC patients with PS 3-4 were selected from different treatment groups. They were comparable in age, sex, etiologies of liver disease, severity of cirrhosis, tumor burden, and prevalence of diabetes mellitus (all P >0.05) at baseline. In the matching model, patients with PS 3-4 undergoing supportive care had significantly shortened survival with an adjusted hazard ratio of 4.711 (confidence interval: 3.041-7.297, P <0.0001). Conclusions: Over one-third of patients with PS 3-4 receive active anti-HCC treatments against the BCLC allocation algorithm in this study. Active anticancer therapies rather than best supportive care should be performed if there is no apparent contraindication.